Stability Analysis of Finance System Model with Information Effect - Vivi Aida Fitria; Yudistira Arya Sapoetra (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2020)
Indonesia's participation in investing in the capital market is still very low, one of the causes is the lack of information. So this study discusses the analysis of stability in the financial system if influenced by information. We find that the model has two equilibrium point, that are point without interest rates and the price index of financial instruments and then the existing point of interest rates, the level of investment demand, price indexes and the influence of control input the information. The results of the local stability analysis of the equilibrium points are stable with certain conditions. The analytical result are confirmed by numerical simulations.